The Impact of Food Label Perception and Nutrition Literacy on Communication Behavior : A Case Study of Medan State University Students - Dina Puspita Sari Daulay; Lismawarni Lismawarni; Rita Hartati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study aimed to investigate the correlation between food label perceptions, nutritional literacy, and communication behaviors among students at Medan State University. Given the growing importance of food literacy for public health, this research sheds light on the challenges that university students face in comprehending and utilizing information from food labels. Employing a qualitative methodology grounded in thematic analysis, data were gathered through an online survey involving 30 students representing diverse academic disciplines. Findings indicate that while a majority of participants possessed a moderate level of understanding regarding food labels, there existed gaps in comprehending crucial aspects such as Daily Value (%DV). Food labels often serve as a tool for fostering conversations about healthy eating, yet their consistent utilization remains limited. In conclusion, this study underscores the necessity for a structured nutrition literacy program to enhance students' capacity for making well-informed nutritional choices and cultivating more robust communication practices of nutrition. The insights gleaned from this study carry implications for shaping educational policies and curricula that more comprehensively integrate food literacy.